MDCT DIAGNOSTICS IN TOTAL KNEE ARTHROPLASTY - Stojadinovic, Milica (Medicinski podmladak, 2024)
The prevalence of osteoarthritis as a degenerative disease of the knee is constantly increasing. More than 50% of over-65s have radiographics characteristics of osteoarthritis (1). It is estimated that the number of total knee arthroplasty (TKA) procedures will increase by 673%, and the TKA revisions will increase by 601% between 2005. and 2030 (28). The three articular surfaces of the knee are replaced by the placement of three appropriate prosthetic components. There is a definite link between the accuracy of the implant position and the long term of the prosthesis (4).The "Perth CT protocol" in addition to the methods of conventional, "long-leg" radiography and CT scans provides the best available means for adequate assessment of  alignment. It involves CT examination of the exterior from the acetabular roof to the talus arch, in supination, neutral position of the leg and maximum knee extension. Post procedural, by reformation in the coronal, sagittal and axial planes, seven alignment characteristics, the mechanical and anatomical axis of the leg are determined (5). The effective dose of radiation at long-leg radiography is about 0.7 mSv, and in the Perth CT protocol about 2.7 mSv (9).The recommendations of the International Commission on Radiation Protection represent two established to princes in radiation protection during medical exposure: the justification of examination and the optimization of protocols. Image quality and radiation dose during CT scan directly depend on the parameters of image acquisition and reconstruction. Optimization involves the selection of parameters of the examination protocol such that the patient dose is as low as possible, and that the diagnostic quality of the image remains satisfactory - ALARA (As Low As Reasonably Achievable) principle (23).
Keywords: total knee arthroplasty, Perth CT protocol, optimization